2019
DOI: 10.1155/2019/7567638
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Rectifier K+-Channel Is a Novel Therapeutic Target for Interstitial Renal Fibrosis in Rats with Unilateral Ureteral Obstruction

Abstract: Background Delayed rectifier K+-channel, Kv1.3, is most predominantly expressed in T-lymphocytes and macrophages. In such leukocytes, Kv1.3-channels play pivotal roles in the activation and proliferation of cells, promoting cellular immunity. Since leukocyte-derived cytokines stimulate fibroblasts to produce collagen fibers in inflamed kidneys, Kv1.3-channels expressed in leukocytes would contribute to the progression of tubulointerstitial renal fibrosis. Methods Male Sprague-Dawley rats that underwent unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…We have demonstrated in several animal studies that the overexpression of Kv1.3-channels in T-lymphocytes and macrophages is strongly associated with their over-activation and the progression of renal fibrosis (12,13). In these studies, margatoxin, a selective Kv1.3channel inhibitor, actually suppressed the activity of the leukocytes and slowed the progression of renal fibrosis.…”
Section: Itsuro Kazama *mentioning
confidence: 98%
“…We have demonstrated in several animal studies that the overexpression of Kv1.3-channels in T-lymphocytes and macrophages is strongly associated with their over-activation and the progression of renal fibrosis (12,13). In these studies, margatoxin, a selective Kv1.3channel inhibitor, actually suppressed the activity of the leukocytes and slowed the progression of renal fibrosis.…”
Section: Itsuro Kazama *mentioning
confidence: 98%
“…Importantly, inhibition of Kv1.3 channels using the selective blocker margatoxin significantly inhibited renal lymphocyte proliferation and ameliorated the progression of renal fibrosis. Their team further demonstrated the effectiveness of targeting lymphocyte Kv1.3 channels in the treatment of renal fibrosis using the UUO mouse model ( Abe et al, 2019 ). Furthermore, stimulation with TGF-β significantly induced an increase in Kv1.3 density and outward K + current amplitude, and the Kv1.3 channel inhibitor regulated the expression of the TGF-β in mouse microglia ( Schilling et al, 2000 ), hypothesizing that Kv1.3 channel inhibitors have a similar mechanism to alleviate renal fibrosis by regulating the expression of the cytokine TGF-β.…”
Section: K + Channelsmentioning
confidence: 99%
“…Besides that, as one of the inhibitors of delayed rectifier K + -channel, Kv1.3 like margatoxin (Abe et al, 2019 ) and YM58343/BTP2 (Mehrotra et al, 2019 ) were expressed on T lymphocytes, and also found to acute injury and chronic fibrosis in rat kidney. T cell infiltration was decreased by a wingless-type (Wnt)/β-catenin pathway inhibitor, ICG-001, which therefore prevented CKD in a 5/6 nephrectomy model (Xiao et al, 2019 ).…”
Section: Potential Therapies Targeting Lymphocytes Of Aki and Ckdmentioning
confidence: 99%